High expression of HIF-1α alleviates benzene-induced hematopoietic toxicity and immunosuppression in mice. (15th October 2022) - Huang, Jiawei; Pu, Yunqiu; Xu, Kai; Ding, Qin; Sun, Rongli; Yin, Lihong; Zhang, Juan; Pu, Yuepu
Abstract: Benzene exposure can cause pancytopenia and immunosuppression, leading to serious diseases such as aplastic anemia (AA) or acute myeloid leukemia (AML), but the underlying mechanism has not been fully elucidated. Hypoxia-inducible factor 1 (HIF-1) is an important transcription factor that regulates many downstream target genes. In this study, we reported a novel mechanism by which high expression of HIF-1α alleviated benzene toxicity. Mice with high expression of HIF-1α (HIF-1α + ) were obtained by the Tet-on system and doxycycline induction, and they and wild-type (WT) mice were exposed to 150 mg/kg benzene for 0, 1, 3, 7, 10, 14, and 28 days. Dynamic changes in hematopoietic and immune-related indicators and the role of HIF-1α were explored. The level of white blood cells in mice reached the highest level on the third day, and immunity was activated and then suppressed within 10 days. Significant pancytopenia and immunosuppression occurred at 14 days and were more pronounced at 28 days. The levels of HIF-1α, EPO, VEGF, RORγt, and IL-17 in WT mice gradually decreased with increasing benzene exposure days, while the levels of Foxp3 and IL-10 increased. These changes were alleviated in HIF-1α + mice. High expression of HIF-1α increased the levels of EPO and VEGF, which helped to maintain the stability of the hematopoietic microenvironment. Simultaneously, it attenuated benzene-induced immunosuppression by alleviating the Th17/Treg imbalance. HIF-1α is expected to be a new target for benzene-induced diseases such as AA and AML. Graphical abstract: Image 1 Highlights: Immunity levels fluctuated in mice during 10 days of benzene exposure. High HIF-1α expression alleviated pancytopenia by increasing VEGF and EPO levels. High HIF-1α expression alleviated the benzene-induced Th17/Treg immune imbalance.